Children's Disclosures of Physical Abuse in a Population-Based Sample. Issue 5 (March 2022) - Lahtinen, Hanna-Mari; Laitila, Aarno; Korkman, Julia; Ellonen, Noora; Honkalampi, Kirsi
Few studies have explored the disclosure of child physical abuse although child sexual abuse disclosure has been widely studied and debated for years. The present study explores the characteristics of child physical abuse disclosures and compares them to previously published findings on child sexual abuse disclosure from the same data. The data consist of a representative sample of 11, 364 sixth and ninth graders. Participants responded to a wide variety of questions concerning experiences of violence, including child physical abuse and child sexual abuse, in the Finnish Child Victim Survey conducted in 2013. Within this sample, the prevalence of child physical abuse was 4.1%. Children reporting abuse experiences also responded to questions regarding disclosure, reactions encountered during disclosure, and potential reasons for nondisclosure. Findings show that most of the children who disclosed physical violence had disclosed to their mother. The overall disclosure rate of child physical abuse was 74%. However, only 42% had disclosed to adults, and even fewer had reported their experiences to authorities (12%). The most common reason for nondisclosure was that the youth did not consider the experience sufficiently serious to report (53%). These findings were largely in line with the child sexual abuse disclosure rates in our previous study. Analyses of variables associated with disclosing to an adult indicate that the strongest factors predicting disclosure to an adult are younger age, female gender, no previous experiences of child physical abuse, and parents knowing who their child spends her or his spare time with. Implications for further research and practice are discussed.